DETERMINATION OF STRESS FACTORS ACCORDING TO VARIABLES AND INVESTIGATION OF THEIR RELATION TO EMPATHETICAL INCLINATION OF KARATE REFEREES - Bekir Barış CİHAN; Ebru ARAÇ ILGAR (International Journal of Eurasia Social Sciences, 2018)
The aim of this research is to determine the stress factors of the karate judges according to different variables and the relation with the level of empathic inclination. The sample of the research consist of 17 women and 81 men who work in international, national and regional matches (N = 98) as karate referees in different region of Turkey during 2016- 2017 seasons. As data collection scales "stress factor scale for football referees" which created by Çakmak (2011) and ”Empathic inclination Scale" created by Dökmen (1988) were used. Analysis of the data showed that the average individual stress level of female judges and the environmental stress scores of the female referees were higher than the average scores of male referees in environmental stress points . When the relationship between the empathy scores of the referees and the individual and organizational stress factor scores were examined, there was a negative and low level relationship between empathy levels and individual- environmental stress levels. As a result; when the stress sources of karate referees were examined, it can be said that significant differences were found according to gender, age, marital status and experience as referee variables, and the level of empathic inclination has no effect on the stress factors.